El superlativo relativo, ¿comparativo o superlativo?: Una vieja polémica gramatical - Sánchez Salor, Eustaquio (1996)
Since Greek authors is has been traditionally agreed that comparison is a three degree-system: positive, comparative and superlative. Doctrine also argues that superlative can compare, specially in case of relative superlative, which compares a tem with another of the same category. According to this doctrine, relative superlative is, therefore, a comparative rather than an elative. Against this traditional idea, the most rational grammatic since Prisciano to Brocense argues that superlative, even the relative one, is superlative and not comparative and that the genitive that sometimes depends on it is not a second term of comparison, but a partitive. This idea is based on two arguments: first, the functions which doctrine ascribes to relative superlative -for example, to connect a tem with another of the same category- can also be worded by a comparatife and, hence, superlative is not needed for this function and the compolement which depends on a comparative is not a second term of comparison but a partitive, so that the complement which depends on a relative superlative must be aso partitive and not comparative. Second, it is necessary to prove with some texts that tripartite system of comparison, in fact does not exist: that is to say that texts and facts demonstrate that comparative is comparative and superlative, even relative superlative, is superlative. We believe that true is, as always, in aurea mediocritas.
Keywords: Gramática